Evaluation of a Novel Protocol for Assessment and Treatment of Alcohol Withdrawal Syndrome in Psychiatric Inpatients - Butterfield, Michael (Am J Addict, 2020)
BACKGROUND AND OBJECTIVES: Despite the high incidence of alcohol withdrawal syndrome (AWS) in psychiatric inpatients, standardized methods for assessing and treating AWS have been studied only once before in this population. We evaluated a novel AWS assessment and treatment protocol designed for psychiatric inpatients. METHODS: This retrospective cohort study evaluated outcomes before and after implementation of the protocol. We collected consecutive data on patients (N = 138) admitted to inpatient psychiatric units at a single center. Participants were patients admitted for nonsubstance-related psychiatric reasons, who were also at risk for developing AWS. Those who developed AWS were treated with either (a) treatment as usual (TAU) or (b) a novel standardized protocol. The primary outcome was duration of benzodiazepine treatment for symptoms of alcohol withdrawal. Secondary outcomes included cumulative benzodiazepine dose administered, treatment duration, and incidence of complications. RESULTS: Of 138 participants, 83 received TAU and 55 were assessed and treated with the novel protocol. Median duration of benzodiazepine treatment following protocol implementation was 19.7 hours (interquartile range [IQR], 0-46) prior to implementation (TAU) and 0 hours (IQR, 0-15) following protocol implementation (protocol group) (P < .0001). Median benzodiazepine dose (in diazepam equivalents) administered to participants was 30 mg (IQR, 0-65) for TAU and 5 mg (IQR, 0-30) for the protocol group (P < .001). Adverse events before and after implementation occurred in 4.8% and 0%, respectively (P = .15). CONCLUSION AND SCIENTIFIC SIGNIFICANCE: This study provides preliminary evidence for the efficacy and safety of a novel standardized AWS protocol for psychiatric inpatients. This is the first known study assessing an AWS assessment and treatment protocol designed for psychiatric inpatients.